The underwater survival of adult and larval stages of Argas persicus (Acari: Argasidae) - Mousa Tavassoli; Zahra Rezanejad Sabeghi; Behnaz Ghorbanzadeh; Shokoofeh Shamsi; Jafar Arjmand; Mostafa Golabi (Persian Journal of Acarology)
The soft tick, Argas persicus, is the most important ectoparasite in chicken and other domestic fowl, well as in humans. The main aim of this study was to evaluate the survival rate of A. persicus under three different environmental conditions, including immersion in tap water, immersion in oxygenated water and after being placed and washed along clothes in an ordinary washing machine. Adult and larval ticks were separately immersed in tap and oxygenated water for six different time periods:  1, 6, 24, 48, 72 hours and 1 week. Both adults and larvae survived up to 72 hours immersion in tap water. All the ticks immersed in tap water died during the first week; while 53.3% of adult ticks survived one week immersion in oxygenated water. To evaluate the survival rate of ticks in the washing machine, only adults were used and the ticks were placed in a small hub filter before being placed in a Samsung washing machine  at three different temperatures (30, 40 and 60°C). At the end of each cycle, we counted the surviving ticks.  All ticks survived 30 and 40 °C, while only 13.3% survived at 60 °C. In conclusion, adult and larval stages of A. persicus survived under water for couple of days while washing in regular washing machine did not kill adult ticks under temperatures of 30 and 40 °C. So in order to kill the ticks in clothes temperatures more than 60°C should be used.